ESTIMASI PERIODE RAMP-UP LALU LINTAS JALAN TOL DALAM KOTA - Yussi Meviany; Tri Basuki Joewono; Andreas Wibowo (Jurnal Jalan-Jembatan, 2019)
ABSTRACT In order to increase development, the Government is massively infrastructure. Sources of funding for toll road investments under the Public Private Partnerships (PPP) schemes are mostly derived from loans, thus requiring investors to manage cash flow in order to service debts on time. Revenue has a very significant effect on cash flow, while revenue itself is highly dependent on traffic volume. Hence, the accuracy of forecasting the amount of traffic as a reflection of revenue has an important role in determining the feasibility study of toll road investment. The risk in transportation projects is the duration and significance of the transition period from the initial/start operation to the stable traffic level, this period is known as the ramp-up period. This study uses monthly data on 4 cases study as data entry and analysing in the ‘Minitab’ software. From the regression analysis it is known that the profile of the traffic distribution at toll roads in Indonesia is a concave model which means that the amount of traffic has a tendency to increase from time to time and a significant traffic growth ratio significantly occurs from the start of service opening. The F-test analysis statistically known JORR has the shortest ramp-up duration of 9 months and BORR, Waru-Juanda and Bali Mandara respectively 42, 44 and 48 months. Keywords: ramp-up, toll road, traffic growth, heuristic F-test, regression, traffic risk.